Images of Kabīr - Horstmann, Monika (South Asian studies, 2002)
Contributed articles on life and works of Kabir, 15th century Hindi devotional poet, presented at an international symposium commemorating the six-hundred anniversary of Kabir held at Heidelberg in 1999